If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -9 = 3(y + 5) Reorder the terms: -9 + 6y = 3(y + 5) Reorder the terms: -9 + 6y = 3(5 + y) -9 + 6y = (5 * 3 + y * 3) -9 + 6y = (15 + 3y) Solving -9 + 6y = 15 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -9 + 6y + -3y = 15 + 3y + -3y Combine like terms: 6y + -3y = 3y -9 + 3y = 15 + 3y + -3y Combine like terms: 3y + -3y = 0 -9 + 3y = 15 + 0 -9 + 3y = 15 Add '9' to each side of the equation. -9 + 9 + 3y = 15 + 9 Combine like terms: -9 + 9 = 0 0 + 3y = 15 + 9 3y = 15 + 9 Combine like terms: 15 + 9 = 24 3y = 24 Divide each side by '3'. y = 8 Simplifying y = 8
| 15x+64=302 | | 7d=-21 | | 0=9x-56 | | 7t-9=3(y+5) | | (7u-5)^1/2=(9u-15)^1/2 | | 3x+63=84 | | y=-px+q | | 0.09Xx=144.39 | | 19=x-y | | 5(t-2)=1+10 | | 30=5(x+10) | | x+b+c(m)=x | | 3400=x^2+60x+1800 | | 1x=x | | 3x^2-5x-99=0 | | -5/2(5/7) | | y=3/2(x-8) | | 1/3x-6=2 | | 11.4-22.5z=84.1 | | 18-2x=3x-7 | | -12=-3w+-3 | | 5/x-8=6 | | 7(3x-11)-2(-2x-5)+9= | | y=695.6+-0.6c | | 9x/10b*2xb/3x^2 | | 1-4d=-19 | | 1-14=-19 | | 45=.75x | | 5.2x+1=4.2x | | 4x^2=x^2+2 | | -4x+10=-2x-6 | | A*6+8=38 |